Black Campaign tactics in Shaping Perception Voter Beginner (Case Study: Helvetia Village, Medan Sunggal District , North Sumatera) - Febiola Tampubolon, Stevanie; Ivanna, Julia (Ampera: A Research Journal on Politics and Islamic Civilization, 2024)
A black campaign can be interpreted as a deliberate attempt to undermine an opponent using baseless negative arguments. Traditionally, black campaigns were conducted through whisper campaigns, spreading rumors from person to person. However, these campaigns have become more sophisticated with the use of electronic media. This study employs a qualitative method, conducting interviews and referencing additional journal sources. The research findings indicate that black campaigns are not only manifested in the form of posters or banners, as observed in the village of Srigading, but also frequently occur on social media. Social media exerts a significant impact on society, especially among younger generations who are the primary consumers. The influence of social media as an educational communication medium allows users to express opinions and share information with one another.